Mediation law and civil practice - Allen, Tony (London : Bloomsbury Professional, 2019)
Mediation Law and Civil Practice examines the position of mediation within the civil justice system in England and Wales. It explains and challenges current thinking about mediation, identifying ways for the government and judiciary to improve the delivery of justice through greater trust in the process. It traces the evolution of the relationship between the courts and mediation, discussing all the significant judgments relating to mediation over the last 25 years as well as exploring the key concepts at the heart of mediation and all the latest developments. Mediation Law and Civil Practice also challenges the status quo by casting doubt on some decisions and generates alternative thinking around current legal and practice concepts. As well as updating all case law, the second edition also: - discusses the attitudes generated by the Jackson Review and also the Briggs reforms proposed in the Chancery Modernisation Review and his Court Structure Review - discusses AB v CD, in which a mediator has now given evidence in an English court and Global and related cases on varying "whole agreement" clauses - enlarges the discussion of protocols, which have been modified and remain inconsistent in their treatment of ADR - analyses the EU Consumer Directive - sets out the reforms to CPR Part 36 Mediators, mediation providers, lawyers, judges academics and students will all benefit from the expert commentary and in-depth analysis in this book. It is also a useful guide for academics and mediation providers outside of the UK who are seeking to influence the development of mediation in their jurisdictions.
Previous edition: 2013.
Includes bibliographical references and index.
oif 17/12/2019
Loans
Keywords: Mediation; Civil law; England; Wales